Conscious capitalism : liberating the heroic spirit of business - Mackey, John, 1954-; Sisodia, Rajendra (Boston, Mass. : Harvard Business Review Press, 2013)
In this book, Whole Foods Market cofounder and professor and Conscious Capitalism, Inc. cofounder argue for the inherent good of both business and capitalism. Featuring some of today's best-known companies, they illustrate how these two forces can, and do, work to create value for all stakeholders: including customers, employees, suppliers, investors, society, and the environment. These companies include Whole Foods Market, Southwest Airlines, Costco, Google, Patagonia, The Container Store, UPS, and dozens of others. We know them; we buy their products or use their services. Now it's time to better understand how these organizations use four specific tenets: higher purpose, stakeholder integration, conscious leadership, and conscious culture and management, to build strong businesses and help advance capitalism further toward realizing its highest potential. As leaders of this movement the authors argue that aspiring leaders and business builders need to continue on this path of transformation for the good of both business and society as a whole. This book advances both a bold defense and reimagining of capitalism and a blueprint for a new system for doing business grounded in a more evolved ethical consciousness. It provides a new lens for individuals and companies looking to build a more cooperative, human, and positive future.
Foreword: Getting capitalism back on track, by Bill George -- Introduction: Awakenings -- 1. Capitalism: marvelous, misunderstood, maligned -- 2. Conscious capitalism and the heroic spirit of business -- Part One. The First Tenet: Higher Purpose -- 3. Purpose: the corporation's search for meaning -- 4. Discovering and growing purpose -- Part Two. The Second Tenet: Stakeholder Inegration -- 5. Loyal, trusting customers -- 6. Passionate, inspired team members -- 7. Patient, purposeful investors -- 8. Collaborative, innovative suppliers -- 9. Flourishing, welcoming communities -- 10. A healthy, vibrant environment -- 11. The outer circle of stakeholders -- 12. The interdependence of stakeholders -- Part Three. The Third Tenet: Conscious Leadership -- 13. The qualities of conscious leaders -- 14. Becoming a conscious leader -- Part Four. The Fourth Tenet: Conscious Culture and Management -- 15. Conscious cultures -- 16. Conscious management -- 17. Becoming a conscious business -- 18. The power and beauty of conscious capitalism -- The conscious capitalism credo -- Appendix A. The business case for conscious capitalism -- Appendix B. Conscious capitalism and related ideas -- Appendix C. Misconceptions about conscious capitalism.
Includes bibliographical references (pages 307-322) and index.
Keywords: Social responsibility of business; Business ethics; Capitalism -- Moral and ethical aspects; Corporations -- Moral and ethical aspects; Social values